ERYTHROCYTES AGGREGABILITY AND INTRACARDIAC HEMODYNAMICS IN PATIENTS WITH ATRIAL FIBRILLATION (World Science, 2022)
According to the World Health Organization the morbidity of atrial fibrillations is 1-2% of the general population, which is extremely high number due to the severity of the disease. The frequency of morbidity will increase by about 2.5 times (1). Namely, the unfavorable epidemiological picture of atrial fibrillation makes the project relevant. There are numerous studies, although intracardiac hemodynamics and hemorheologycal parameters and their role in the course of atrial fibrillation have not been studied; We have studied the hemorheological profile in patients with atrial fibrillation. Changes of rheological parameters and hemodynamics were assessed against the background of rhythm disturbances. We examined 50 patients (women-22, men - 28, the average age of 65±10) and 20 healthy volunteers. We have studied the Index of the Erythrocytes aggregability, which is the area of aggregated erythrocytes divided by the full area of the erythrocytes. These new innovative methods “Georgian Technique” is created by Georgian scientists and they are famous in the world as direct, numeral and exact [G. Mchedlishvili, 2004; N. Maeda, 2010; M. Mantskava M., 2011]. Also, all patients the studies: ECG, ECHOcardioscopy was performed. After statistical processing of the material, it was found that erythrocytes aggregability is highly impaired in patients with permanent and persistent forms of atrial fibrillation. Mean value of EAI is 41.7 ± 10.4 compared to the control group, where the average EAI value is within 25.6 ± 1.2. The Index of erythrocytes aggregability (EAI) are significantly increased in inverse proportion to the decrease of the left ventricular ejection fraction. A negative correlation was revealed between the Index of erythrocytes aggregation and the left ventricular ejection fraction (R=0.4); According to the obtained data, changes of rheological parameters deepen in the wake of disruption of intracardiac hemodynamics; This confirms the notion that a small blood vessel is the "target" in the case of atrial fibrillation. From hemodynamic mechanisms rheology plays an important role. They are determinants of hemodynamic processes in the body (2).